2002
DOI: 10.1136/jnnp.72.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing antiepileptic drugs in patients who are seizure free on monotherapy

Abstract: Objectives: To assess the recurrence rate of epilepsy attributable to discontinuation of treatment in seizure free patients and to identify the risk factors for recurrence. Methods: 330 patients referred to an epilepsy centre who were seizure free for at least 2 years while on stable monotherapy were the study population. Discontinuation of antiepileptic drugs (AEDs) was proposed to all eligible patients or to their carers after discussion of the risks and benefits. Depending on whether they accepted or refuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
55
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 25 publications
6
55
0
5
Order By: Relevance
“…While some studies show that within the NCS/NCSE group, subjects with generalized ictal discharges had a worse prognosis compared to subjects with unilateral ictal discharges [34], others did not find any prognostic correlation with abnormal or epileptiform EEG [31]. In the context of AED withdrawal, a number of studies have identified factors associated with increased risk of relapse including multiple seizure types, focal epileptiform abnormalities on EEG, and worsening EEG patterns after AED discontinuation [29,[35][36][37]. While we did not analyze outcomes based on NCS/NCSE subtypes, we did find that the primary background EEG abnormality was similar to previously published studies and did not differ between the wean and non-wean groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies show that within the NCS/NCSE group, subjects with generalized ictal discharges had a worse prognosis compared to subjects with unilateral ictal discharges [34], others did not find any prognostic correlation with abnormal or epileptiform EEG [31]. In the context of AED withdrawal, a number of studies have identified factors associated with increased risk of relapse including multiple seizure types, focal epileptiform abnormalities on EEG, and worsening EEG patterns after AED discontinuation [29,[35][36][37]. While we did not analyze outcomes based on NCS/NCSE subtypes, we did find that the primary background EEG abnormality was similar to previously published studies and did not differ between the wean and non-wean groups.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, the bias is toward an increased risk of seizure recurrence following AED discontinuation [28]. Both randomized controlled trials and prospective studies have demonstrated that adult patients with known epilepsy who continue AED treatment have relapse rates of 22-28%, compared with 41-50% in withdrawal groups [29,30] although lower seizure relapse rates of 15% have been reported in AED withdrawal groups [31]. Our study found a relapse rate of approximately 15% overall (17% and 13% in wean and non-wean groups, respectively) during the remainder of hospitalization after a seizure-free interval of at least 24 h. This lower rate compared to outpatient studies may be due, in part, to the shorter monitoring period which, by default, does not account for the long-term follow up times that were used in the outpatient population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a metaanalysis, the risk of relapse after AED withdrawal was 25% after 1 year and 29% at 2 years. 21 Specchio et al 22 found that the risk of seizure relapse after discontinuing treatment was 2.9 times that of patients continuing treatment. Our study supports the evidence of the difficulties that are associated with discontinuing AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…Complications from longstanding treatment with some AEDs are well described, but relatively few studies exist to establish the risks of tapering AEDs in medically managed seizure-free adults (1)(2)(3)(4)(5). A systematic meta-analysis has identified a relapse rate of 29% (5), whereas the prospective studies have identified relapse rates of 27 to 52 percent (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…A systematic meta-analysis has identified a relapse rate of 29% (5), whereas the prospective studies have identified relapse rates of 27 to 52 percent (1)(2)(3)(4). Literature reviews on this topic have occurred in the past (6)(7)(8), and the relative safety of withdrawal of AEDs in the setting of 2 or more years of seizure freedom has been reported.…”
mentioning
confidence: 99%